2022
DOI: 10.1038/s41416-022-01823-5
|View full text |Cite
|
Sign up to set email alerts
|

BRCA mutations lead to XIAP overexpression and sensitise ovarian cancer to inhibitor of apoptosis (IAP) family inhibitors

Abstract: Background We tested the hypothesis that inhibitor of apoptosis family (IAP) proteins may be altered in BRCA1-mutated ovarian cancers and that could affect the sensitivity to IAP inhibitors. Methods The levels of IAP proteins were evaluated in human cancers and cell lines. Cell lines were used to determine the effects of IAP inhibitors. The in vivo effects of treatments were evaluated in PDX mouse models. Results Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…[89] HTRA and SMAC genes also function as inhibitors of IAP in apoptosis activation. Increased IAP expression has been linked to poor prognosis in esophageal [90,91] and breast [92] cancers. Several studies have suggested that heat shock proteins (HSPs) may shield mitochondrial functions and prevent apoptotic signals in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…[89] HTRA and SMAC genes also function as inhibitors of IAP in apoptosis activation. Increased IAP expression has been linked to poor prognosis in esophageal [90,91] and breast [92] cancers. Several studies have suggested that heat shock proteins (HSPs) may shield mitochondrial functions and prevent apoptotic signals in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research in recent years has illustrated a link between alterations in IAP expression and the onset and progression of tumours, as well as medication resistance. Researchers have found that BRCA mutations lead to XIAP overexpression, making ovarian cancer sensitive to the IAP family [ 12 ]. BIRC5 stimulates cellular apoptosis, diminishes the growth capacity of tumours, and renders cancerous cells more susceptible to chemotherapeutic agents (e.g., etoposide, Taxol, cisplatin), immunotherapy, and gamma radiation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has revealed that the IAP family plays a role in cell cycle regulation, cell migration, and other biological processes [ 9 11 ]. Aberrant expression of its members is linked to the development of tumours [ 12 15 ] and can serve as tumour markers [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence demonstrates that XIAP promotes the growth, invasion, and metastasis of malignant cells, confers resistance to certain chemotherapeutic drugs, and associates with poor outcome in a variety of cancers 3,4 . Overexpression of XIAP is frequently observed in human cancers and may contribute to tumorigenesis by evading cancer cell apoptosis 5,6 . As for AML, multiple reports have regarded XIAP as a unfavourable gene through a variety of signal pathways, including caspase pathway 7,8 and NF‐kB pathway, 9 and inhibition of XIAP can sensitize AML cells to tumour necrosis factor‐related apoptosis‐inducing ligand (TRAIL) 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Overexpression of XIAP is frequently observed in human cancers and may contribute to tumorigenesis by evading cancer cell apoptosis. 5,6 As for AML, multiple reports have regarded XIAP as a unfavourable gene through a variety of signal pathways, including caspase pathway 7,8 and NF-kB pathway, 9 and inhibition of XIAP can sensitize AML cells to tumour necrosis factor-related apoptosis-inducing ligand (TRAIL). 10,11 Recently, several studies also show that XIAP inhibitors can increase the efficacy of BCL2 inhibitors 12 or affect AML myelomonocytic differentiation.…”
Section: Introductionmentioning
confidence: 99%